Corporate Governance and Ethical Leadership: Key Factors in Preventing Financial Statement Fraud and Money Laundering - Hussein, Qutaib; Mustawfyah, Sharif; Efstath Haneh, Fazıl (Inovasi Analisis Data, 2024)
Purpose: This study examines the role of GCG and EL in preventing accounting fraud and money laundering in Iraqi firms. It examines how these factors contribute to improving financial integrity and organisational performance.Method: A sample of 38 companies in Iraq was selected based on specific criteria. Data were analysed using regression models to assess the impact of GCG, EL and other financial variables on the prevention of fraud and money laundering.Findings: The results show that robust corporate governance and ethical leadership significantly reduce financial misconduct. The interaction between GCG and EL has a synergistic effect, improving organisational transparency and performance.Novelty: This study provides new insights into the Iraqi context, highlighting the combined impact of governance and leadership on financial crime prevention, a perspective underexplored in emerging markets.Implications: The findings highlight the importance of strengthening governance structures and ethical leadership to combat financial crime. This research provides a foundation for future studies and offers actionable recommendations for policymakers and business leaders to promote integrity and transparency in corporate practices.